Evolutionary dynamics of the human pseudoautosomal regions - Monteiro, B (2021)
Recombination between the X and Y human sex chromosomes is limited to the two pseudoautosomal regions (PARs) that present quite distinct evolutionary origins. Despite the crucial importance for male meiosis, genetic diversity patterns and evolutionary dynamics of these regions are poorly understood. In the present study, we analyzed and compared the genetic diversity of the PAR regions using publicly available genomic sequences encompassing both PAR1 and PAR2. Comparisons were performed through allele diversities, linkage disequilibrium status and recombination frequencies within and between X and Y chromosomes. In agreement with previous studies, we confirmed the role of PAR1 as a male-specific recombination hotspot, but also observed similar characteristic patterns of diversity in both regions although male recombination occurs at PAR2 to a much lower extent (at least one recombination event at PAR1 and in ˜1% in normal male meioses at PAR2). Furthermore, we demonstrate that both PARs harbor significantly different allele frequencies between X and Y chromosomes, which could support that recombination is not sufficient to homogenize the pseudoautosomal gene pool or is counterbalanced by other evolutionary forces. Nevertheless, the observed patterns of diversity are not entirely explainable by sexually antagonistic selection. A better understanding of such processes requires new data from intergenerational transmission studies of PARs, which would be decisive on the elucidation of PARs evolution and their role in male-driven heterosomal aneuploidies.